Type designation for Cyclachaena xanthiifolia (Euphrosyne xanthiifolia) (Heliantheae, Asteraceae) - Crespo, Manuel B.; Pena-Martín, Carolina; Becker, Anna Sarah; Dressler, Stefan (Phytotaxa, 2015)
Cyclachaena xanthiifolia (Iva xanthiifolia) is a North American member of the Heliantheae-Ambrosiinae (Asteraceae), which is currently accepted in the genus Euphrosyne. It is a nitrophilous plant, usually growing in disturbed grounds related to human activities, and this fact has probably favoured its introduction and naturalization in Eurasia and New Zealand. As part of the taxonomical work on the Iberian Compositae, typification of the name Cyclachaena xanthiifolia is effected here by selection of a lectotype and an epitype from the material housed at FR (Frankfurt am Main, Germany). The protologue and original material are discussed, and pictures of the relevant material are presented. Some historical aspects are also discussed to justify typification.